Perfil psicossocial de mulheres durante o pré – natal em um hospital de referência do sistema de saúde pública do Brasil - GOMES, Franco Celso da Silva (2018)
Gestation is a physiological event in a woman's life, marked by intense physical, psychological, social and economic changes. Emotional aspects are a challenge, with the possible stress, lack of social support and self-esteem that are disruptive to maternal health and well-being where prenatal care is integral to a safe and healthy pregnancy. Thus, the general objective of this study was to evaluate the psychosocial profile of pregnant women under prenatal care from the Prenatal Phycossocial Profile (PPP). The methodology applied in this study is cross - sectional, descriptive, exploratory, with primary data collection from March to July 2017, at the Obstetrics Outpatient Clinic of HUUFMA, in the city of. With pregnant women who were in prenatal follow-up. For the research, a questionnaire validated, adapted and translated into Portuguese, was used (PPP-VP). The sample consisted of 160 pregnant women, including all women between the ages of 14 and 47 years. In the descriptive statistical analysis it can be observed that the characterization of the sample was mostly evidenced that the pregnant women had full secondary education, age group of 15 to 35 years, were in the third trimester of gestation, primigravidae, with number of pre - In the linear regression analysis of the stress construct all variables had a significant influence, with emphasis on financial concerns (R2 = 0.60), on the social support of the companion and other people, all items of the construct influenced significantly. All the variables that make up the self-esteem construct had a significant influence, and the simple linear regression revealed that the feeling that "no" is a failure (R2 = 0.37) and feel satisfied with itself (R2 = 0 , 31) were the ones that most explicitly explained this construct. In Pearson 's correlation, stress and self - esteem was the only one that showed a negative correlation and a strong influence (r = - 0.178 / p = 0.025). The analysis of variance shows that there were no differences of statistical significance between the gestational trimesters relative to PPP-VP. Also related to the instrument when relating parity and elements of the construct was evidenced influence of stress mainly in multiparous women. The study shows that pregnant women have psychosocial factors adjusted and within a pattern that does not compromise the period, but there is still very little talk in the units of this look about these aspects which can cause negative interferences to gestation.